Protease-Activated Receptor 2 Activation Inhibits N-Type Ca2+ Currents in Rat Peripheral Sympathetic Neurons - Kim, Young-Hwan; Ahn, Duck-Sun; Kim, Myeong Ok; Joeng, Ji-Hyun; Chung, Seungsoo (Molecules and cells, 2014)
The protease-activated receptor (PAR)-2 is highly expressed in endothelial cells and vascular smooth muscle cells. It plays a crucial role in regulating blood pressure via the modulation of peripheral vascular tone. Although several mechanisms have been suggested to explain PAR-2-induced hypotension, the precise mechanism remains to be elucidated. To investigate this possibility, we investigated the effects of PAR-2 activation on N-type Ca(2+) currents (I(Ca-N)) in isolated neurons of the celiac ganglion (CG), which is involved in the sympathetic regulation of mesenteric artery vascular tone. PAR-2 agonists irreversibly diminished voltage-gated Ca(2+) currents (I(Ca)), measured using the patch-clamp method, in rat CG neurons, whereas thrombin had little effect on I(Ca). This PAR-2-induced inhibition was almost completely prevented by ω-CgTx, a potent N-type Ca(2+) channel blocker, suggesting the involvement of N-type Ca(2+) channels in PAR-2-induced inhibition. In addition, PAR-2 agonists inhibited I(Ca-N) in a voltage-independent manner in rat CG neurons. Moreover, PAR-2 agonists reduced action potential (AP) firing frequency as measured using the current-clamp method in rat CG neurons. This inhibition of AP firing induced by PAR-2 agonists was almost completely prevented by ω-CgTx, indicating that PAR-2 activation may regulate the membrane excitability of peripheral sympathetic neurons through modulation of N-type Ca(2+) channels. In conclusion, the present findings demonstrate that the activation of PAR-2 suppresses peripheral sympathetic outflow by modulating N-type Ca(2+) channel activity, which appears to be involved in PAR-2-induced hypotension, in peripheral sympathetic nerve terminals.